The Relationship Between Education Expenditure, Capital And Labour Force Towards Economic Growth In Malaysia - Yvonne Gillian, Anak Nelson (Universiti Malaysia Sarawak, (UNIMAS), 2019)
The general objective of this study is to determine the relationship between education expenditure, capital and labour force towards economic growth in Malaysia. In this study, the annual data of time series was used from year 1982 until year 2015. The test used to determine the result of this study is consists of unit root test, co-integration test and Granger Causality. This study found four co-integration test by using the Johansen and Juselius Co-integration test to determine the co-integration vectors. This method has achieved the specific objective of this study by having at least one co-integration vector to determine the long run relationship between the dependent variable and the independent variable. The study found that school enrollment for secondary education and tertiary education has a bidirectional long run relationship toward the GDP per capita and school enrollment for secondary education has a unidirectional short run relationship toward labour force which contributes to the GDP per capita. Hence, the capital development and labour force has a positive relationship toward economic growth in Malaysia while education expenditure has a negative relationship toward economic growth in Malaysia. Therefore, Malaysia government in need to implement and introduce a new ways and solutions in increasing and enhancing the quality of education system in producing a multi intellectual capital in contributing toward economic growth.